Legumes as a Cornerstone of the Transition Toward More Sustainable Agri-Food Systems and Diets in Europe - Ferreira, Helena; Pinto, Elisabete; Vasconcelos, Marta W. (Frontiers in Sustainable Food Systems, 2021)
Legume grains are important sources of nutrients in human and animal diets and have been so for millennia. Their history as part of traditional diets dates to the origins of agriculture when their benefits for soil health and agricultural productivity started to be realized, mostly empirically, by farmers. In time, legumes have lost their popularity as human food, either because of a negative connotation as “poor man's meat,” occasional gastrointestinal side effects, or habitually longer preparation times when compared to other types of plant foods. Also, the steep rise in the consumption of meat derived foods in the last half of a century has taken a toll on replacing legumes as a major protein source. Alongside this negative trend in consumption, a negative drift in production was also observed, especially in Europe, where legumes currently occupy a minimal fraction of agricultural land. One of the main factors is a loss in competitive edge amongst farmers due to sustained lower public and private investments in breeding programs and legume adapted technology for planting, managing, harvesting, processing, and storing, when compared to cereals. Recently, increased awareness of the need to move to sustainable food systems is revitalizing legume production and consumption in Europe, leading to a compilation of policies and initiatives that aim to put legumes again as foundations for this transition. Legumes have been reinvented in a multitude of products (drinks, cereal bars, bread, meat replacers, snacks, flours, and several others) and included in farming systems of conservation agriculture, organic production, intercropping, and crop rotation, combining ancient traditions of legume production “with a spin,” incorporating new legume technological knowledge in farming systems. However, the transition has been slow and hampered by many cultural, societal, political, and economic impediments. This paper summarizes initiatives that aim to enable the comeback of legumes and their placement in a more prominent position in human diets and agricultural fields and highlights strategies that aim at overcoming the obstacles that impede achieving the development of more sustainable agri-food systems and sustainable diets in Europe.